Meningkatkan Kreativitas dan Kolaborasi Siswa Melalui Implementasi Project Based Learning dalam Proses Pembelajaran PAI - Miftah Falah Udwi Syarfiah; Zahra Nur Azizah; Hoerotunnisa; Tarsono, Tarsono; Siti Nurhuda Abd Wahid (Yayasan Cendekia Gagayunan Indonesia, 2025)
Project Based Learning research is an innovative learning model that emphasizes students in solving a problem by producing a product, making decisions, conducting investigative activities so that creativity and motivation of students increase. The teacher as a facilitator gives students assignments to develop their potential. The stages in Islamic Religious Education learning using the project-based learning model are as follows. 1) Determining basic questions, 2) Making product design plans. 3) Preparing a product manufacturing schedule. 4) Monitoring student performance and project progress. 5) Assessment of results. 6) Evaluation of learning experiences. The implementation of this project-based learning model can be used in Islamic Religious Education materials including Akidah Akhlak, SKI, Fiqh and Qurdits. The purpose of this learning is for students to be able to conclude the material from their direct experience. However, in the implementation process, of course, there are still some obstacles. So that teachers are expected to be mentors and facilitators during the learning process. There are many learning methods that can be used during learning, one of which is PjBL. This study aims to determine the benefits of implementing PjBL for Islamic Religious Education subjects during learning. The data collection method used is a literature study through books, journals, and field research results conducted by previous researchers that are relevant to this study. The results of the study indicate that the implementation of the PjBL model can significantly increase students' creativity in conveying ideas and creating original learning products. In addition, student collaboration has also increased, as seen from their ability to work together in groups, divide tasks, and support each other in the process of completing projects. Thus, the Project Based Learning model has proven effective in increasing student creativity and collaboration in Islamic Religious Education learning.